Utilization of Mill Scale Waste as Natural Fine Aggregate Replacement in Mortar: Evaluation of Physical, Mechanical, Durability, and Post-Fire Properties - Apinun Siriwattanakarn; Ampol Wongsa; Nawapak Eua-Anant; Vanchai Sata; Piti Sukontasukkul; Prinya Chindaprasirt (Recycling)
The current paper presents the findings from experiments focused on using mill scale waste (MSW) as a natural fine aggregate (NFA) replacement in making cement mortar, aiming to recycle this material. Mortars were prepared by mixing with ordinary Portland cement, NFA, and water. NFA was replaced with 5%, 10%, 15%, and 20%vol of MSW. The physical and mechanical properties of mortars including compressive and flexural strengths, density, porosity, water absorption, ultrasonic pulse velocity, thermal conductivity, durability properties, and characteristics after being subjected to elevated temperatures at 400, 700, and 1000 °C were investigated after 28 days of curing. The results showed that 15% MSW exhibited optimum compressive and flexural strengths. Also, the MSW mortar showed reduced workability and thermal conductivity, while the porosity slightly increased. The addition of MSW enhanced chloride resistance and mortar’s residual compressive strength after exposure to various temperatures. These findings confirmed that MSW can be used as a sustainable fine aggregate to produce mortar with optimum physical, mechanical, durability, and post-fire properties.